2015
DOI: 10.5455/medarh.2015.69.127-129
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Among Students at the University of Tuzla

Abstract: Introduction:Cigarette smoking among students is greatly widespread. Smoking prevalence ranges from 28% to 67% for students, respectively, from 19% to 34% for female students.Aim:The aim of this survey was to investigate the smoking habits of students, who are studying at three faculties at the University of Tuzla in academic Year 2012/2013 and to investigate whether there is a difference in smoking habits of students from different faculties and observed by gender.Patients and Methods:The study included a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Tobacco smoking among students is hugely widespread; 47.5% of students occasionally observed symptoms like cough attributed to smoking [6]. Most long-term smokers start smoking from 18 to 25 years of age [7].…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco smoking among students is hugely widespread; 47.5% of students occasionally observed symptoms like cough attributed to smoking [6]. Most long-term smokers start smoking from 18 to 25 years of age [7].…”
Section: Introductionmentioning
confidence: 99%
“…A study of over 970 adolescents in Bosnia and Herzegovina, 17 to 18 years old, showed that 30% of young men and 32% of young women smoke (38), and some of them started smoking as early as 13 years of age (39). The incidence of smoking is also reported to be high in Croatia (27.4%) (40) and Kosovo (31% for adolescent males and 40% for adolescent women) (41).…”
Section: Discussionmentioning
confidence: 99%
“…Ö ğ rencilerin %26.0'ı siğara kullanmaktadır (Tablö I). Bösna Hersek'te 2012-2013 yılları arasında yapılan bir araştırmada ö ğ rencilerin siğara içme sıklığ ı %22.8 ölarak bulunmuştur (21). Tu rkiye Yetişkin Tu tu n Araştırması sönuçlarına ğö re, 15-24 yaş ğrubunda her ğu n tu tu n kullanım öranı %27.1 ölup, erkeklerde (%41.5) kadınlara (%13.1) ğö re daha yu ksektir (22).…”
Section: Discussionunclassified
“…Yetişkinler için BKI değ eri 25-29.9 arasında ölanlar hafif şişman, 30 ve u zerinde ölanlar ise şişman kabul edilmektedir (1). 21. yu zyılın en ö nemli töplumsal hastalığ ı ölarak değ erlendirilen öbezitenin sıklığ ı yıldan yıla ğiderek artmaktadır.…”
Section: Introductionunclassified